2018
DOI: 10.1097/aap.0000000000000746
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Paravertebral Block by Anatomic Landmark Technique to Ultrasound-Guided Paravertebral Block for Breast Surgery Anesthesia

Abstract: The trial was registered retrospectively at the Clinical Trial Registry of India, CTRI/2015/05/005774.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…Inadvertent vascular puncture in particular has been reported in 13 publications. [98][99][100][101][102][103][104][105][106][107][108][109][110] These were reported across a range of adult and pediatric populations, under anatomic and ultrasound guidance, during single shot and catheter blocks, and with rates in these reports of between one-in-527 102 and one-in-eight. 105 None of these cases resulted in serious bleeding outcomes, despite the presence of therapeutic anticoagulation in two reports.…”
Section: Paravertebral Blockmentioning
confidence: 99%
“…Inadvertent vascular puncture in particular has been reported in 13 publications. [98][99][100][101][102][103][104][105][106][107][108][109][110] These were reported across a range of adult and pediatric populations, under anatomic and ultrasound guidance, during single shot and catheter blocks, and with rates in these reports of between one-in-527 102 and one-in-eight. 105 None of these cases resulted in serious bleeding outcomes, despite the presence of therapeutic anticoagulation in two reports.…”
Section: Paravertebral Blockmentioning
confidence: 99%
“…12 An RCT comparing the anatomical landmark PVB technique to an ultrasound-guided technique for breast surgery showed that more patients had successful blocks with ultrasound. 13 Pain control, both at rest and movement, was superior and catheter top-ups were less frequent in the ultrasound group.…”
Section: Breast Surgerymentioning
confidence: 88%
“…In a study by Patnaik and colleagues 16 comparing PVB by the anatomic landmark technique to the US-guided technique for breast surgery anesthesia, found that significantly more patients in the US group (34/36, 94.44%) had a successful block compared to the anatomic landmark group (26/36, 72.22%), and significantly more segments were blocked in the US group. The ribs, spinous and transverse processes of the vertebra, costotransverse joints, and pleura were utilized as sonographic landmarks.…”
Section: Discussionmentioning
confidence: 99%